Partial Political Guilt of the Russian Nation in the War with Ukraine - in the Context of Civilization Conditions - Piekarski, Romuald (Sensus Historiae, 2022)
The article is devoted to the issue of political guilt, borne by the nation and citizens. An attempt was made to update the considerations and findings of Karl Jaspers, expressed in his famous work The Problem of Guilt. About Germany's Political Responsibility. The said update consists in applying the concepts developed by Jaspers to the question of the Russians' guilt for the crimes of the present Russian regime. The author concludes that in the context of political guilt and responsibility for the crimes and perversions of the war between Russia and Ukraine, the most important are the civilization patterns that have prevailed there for centuries and the government institutions that constitute it, as well as the customs that exhibit a peculiar constancy. An additional conclusion may be the conviction that in the future with a peaceful face, the nations of the Russian Federation will have to build their state anew, abandoning the fatal imperial tradition, oppressive for their subjects and enslaved nations.